PENGARUH CONTEXTUAL TEACHING AND LEARNING TERHADAP HASIL BELAJAR TEMATIK KELAS IV SDN 54 PONTIANAK BARAT - Andi Wijaya; Siti Halidjah; Hery Kresnadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
Abstract The problem in this research was how the influence of contextual teaching and learning in Thematic Learning against the results of the grade IV elementary school number 54 West Pontianak. The method used was the experiment with forms of Experimental Design Quaisy design non equivalent control group design. The entire population of students of two classes that add up to 57 people, this research sample was grade IV A of 28 people as a class control and grade IV B of 29 people as a class experiment. Hypothesis test results using t-test (Polled Variance) obtained ???????????????????????? = 2.753 while for dk = 55 with significant level α = 5% obtained ???????????????????????? = 1.674, meaning ???????????????????????? > ???????????????????????? , then the Ha received, this proves there was influence contextual teaching and learning in thematic learning. Based on the results of the calculation of effect size obtained ES = 0.67 which included the criteria of medium. Therefore it can be concluded that using Contextual Teaching and Learning in Thematic Learning provide positive influence towards learning outcomes grade IV elementary school number 54 West Pontianak. Key words : Contextual Teaching and Learning, Influence, the results of the thematic learning